(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Nurlaeni Y, Iskandar J, Junaedi DI. 2021. Ethnoecology of Zanthoxylum acanthopodium by local communities around Lake Toba, North Sumatra, Indonesia. Biodiversitas 22: 1806-1818. Zanthoxylum acanthopodium DC., locally known as andaliman, is a typical spice of traditional cuisine of communities living around Lake Toba, North Sumatra, Indonesia. Despite the extensive uses, the ethnoecological study on this plant is relatively scarce. This study aims to conduct ethnoecological studies of the management and cultivation of andaliman plants based on Traditional Ecological Knowledge of local communities of Salaon Dolok Village, a village nearby Lake Toba which has close relationship and intensively cultivated/utilized andaliman in their daily life. This study applied qualitative methods using the combination of direct observation and interviews with 46 selected respondents using snowball sampling. The results of this study showed that the cultivation of andaliman in Salaon Dolok Village was carried out using traditional ways with simple farming practices. These traditional farming models relied on manual farming practices in all farming aspects. The community has local knowledge related to the management of reliable agricultural systems from generation to generation. Andaliman cultivation in Salaon Dolok Village does not need maintenance costs for fertilizers and pesticides. In general, andaliman planting is mostly done in the forest. In general, the people of this village only recognize two kinds of andaliman cultivars, namely Andaliman ’Simanuk’ and Andaliman ’Sihorbo’. The planting is usually carried out during the rainy season to reduce the mortality rate of the planted seedlings. The activity of seedling preparation is carried out in two simple ways. First, most farmers were collected andaliman seeds that grow wild around the existing andaliman plants. The second method is by collecting the seedling that grows from the burning land with some remains of old andaliman plants collected at the edge of the land. Sustainable agriculture should minimize the external input from outside of the agro-ecosystem. Low External Input Sustainable Agriculture (LEISA) emphasizes the efficient use of existing production factors to create sustainable agriculture, including for andaliman agriculture system.